Dampak Ekonomi Pendirian Alfamart Terhadap Usaha Pedagang Kios-Kios Kecil Di Kota Larantuka - Petrus Tribowo Atahili Betan; Antonius Philipus K.Gheta; Nunsio Handrian Meylano (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This research aims to analyze the economic impact of establishing Alfamart on small kiosks in Larantuka City. The problem formulation in this research is the Economic Impact of the Establishment of Alfamart on Small Kiosk Merchant Businesses in Larantuka City. The results of this research aim to obtain information about the economic impact of the establishment of Alfamart on the businesses of small kiosk traders in Larantuka City? To achieve this goal, the research used is field research. Data collection methods use interviews, observation and documentation methods. The data analysis used is a qualitative descriptive method. Based on data analysis, it was concluded that: regarding the impact of the establishment of Alfamart on small kiosks in Larantuka City, there was a negative impact on traders, namely that the majority of small kiosk traders stated that their income had decreased after the existence of Alfamart. This is proven by the decreasing number of commodities purchased.